2020
DOI: 10.3390/ani10081248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymol Addition and Withdrawal on Some Blood Parameters, Antioxidative Defence System and Fatty Acid Profile in Rabbit Muscle

Abstract: Thymol concentrations in rabbit plasma, intestinal wall (IW) and faeces were detected, and the effects of thymol application and withdrawal on biochemical, antioxidant parameters and fatty acids (FA) in blood (B) and muscle (M) were studied. Forty-eight rabbits were divided into two experimental groups (control, C and with thymol 250-mg/kg feed, T). Thymol was administered for 21 days (TA) and withdrawn for seven days (TW). Thymol in plasma correlated with that in the IW (Spearman′s correlation coefficient (rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…IgA is bound to the receptor at the basolateral surface of enterocytes and subsequently crosses the epithelial layer (Macpherson et al, 2001). Based on our detection of thymol in the intestinal wall and its antioxidant effects as confirmed in previous studies by Placha et al (2019) and Bacova et al (2020), we assume that the higher amount of IgA detected in the intestinal wall is the result of thymol sparing effects on enterocytes and consequently of larger amounts of IgA bonding on their surface. Plasma cells which produce IgA are developed from antigen‐stimulated B cells (Tizard, 2004).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…IgA is bound to the receptor at the basolateral surface of enterocytes and subsequently crosses the epithelial layer (Macpherson et al, 2001). Based on our detection of thymol in the intestinal wall and its antioxidant effects as confirmed in previous studies by Placha et al (2019) and Bacova et al (2020), we assume that the higher amount of IgA detected in the intestinal wall is the result of thymol sparing effects on enterocytes and consequently of larger amounts of IgA bonding on their surface. Plasma cells which produce IgA are developed from antigen‐stimulated B cells (Tizard, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Bozkurt et al (2012) suggested the protective properties of bioactive compounds on the intestinal villi, particularly carvacrol, thymol and 1,8‐cineol, which they explained in terms of acceleration in the renewal rate of mature enterocytes as a consequence of the sparing effect of these compounds against oxidative damage. Based on previous results from Bacova et al (2020), who confirmed the alleviation of oxidative damage by means of thymol addition to the rabbit diet, and based on thymol detection in the intestinal wall in our study, we assume it has beneficial effect on enterocytes. In their study Rubió et al (2014) attributed important antioxidant activity to the conjugated form of thymol, thymol sulphate.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Excreted metabolites from enterocytes are converted back to the parent compound and again reabsorbed. Compounds in the liver are metabolized and together with parent compounds are excreted with bile into the duodenum and are then reabsorbed there [ 14 , 17 ]. These repeating processes together with processes of caecotrophy could explain the thymol content in plasma, tissues, and intestinal content after thymol withdrawal, although only in trace amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of thymol in samples of plasma, tissues and faeces was performed using headspace solid-phase microextraction followed by gas chromatography coupled with the mass spectrometry method as described by Bacova et al [ 14 ] and Placha et al [ 15 ]. Briefly, detection and quantification were carried out using a GC/MS (type HP 6890 GC) system coupled with a 5972-quadrupole mass-selective detector (Agilent Technologies GmbH, Wilmington, DE, USA).…”
Section: Methodsmentioning
confidence: 99%